Pengaruh Perawatan Tali Pusat Metode Topikal ASI dan Kasa Kering Terhadap Waktu Pelepasan Tali Pusat Bayi Baru Lahir Persalinan Post SC - Elvi Era Liesmayani; Lisya Octaviana; Erni Naibaho (Jurusan Kebidanan Poltekkes Kemenkes Padang, 2023)
Umbilical cord care aims to prevent infection and accelerate the release of the umbilical cord from the baby's stomach. Aim; Knowing the effect of umbilical cord care on the time of release of the umbilical cord with the topical breastfeeding method and cord care with the dry gauze method at Delima General Hospital. Method; The type of research used was